Implementation of the Independent Learning Curriculum, Independent Campus, Department of Economic Education - Sri Purwaningsih Siswanto; Fransiscus Jani Lumape; Danny J Polii (Indo Publishing, 2026)
This study uses a qualitative approach with a descriptive design to describe and analyze the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) curriculum in the Department of Economic Education, Manado State University. Informants consisted of 15 key informants and 13 supporting informants who were selected purposively based on their knowledge and experience of MBKM. Data were collected through in-depth interviews, participant observation, and documentation studies, then analyzed thematically. The results of the study showed that partners gave positive assessments of morals, ethics, communication skills, discipline, and students' ability to apply learning methods during the MBKM program. Lecturers and coordinators assessed that the conversion of credits, selection of partners, and the suitability of the MBKM curriculum with the study program curriculum were generally very appropriate, although there were challenges in technical standardization and integration of assessments across study programs. From the student side, most understood the concept and objectives of MBKM and actively participated in activities such as internships and village projects. Students considered this program relevant to their career needs and provided practical experience that increased competitiveness in the world of work. However, there was a gap in the dissemination of information and official guidance related to MBKM. Overall, the implementation of the MBKM curriculum in the Department of Economic Education is considered successful in forming professional competencies and student character that are in accordance with the needs of the world of education and the world of work, although improvements are needed in the alignment of the curriculum and socialization of the program.